Hubungan Intensitas Penggunaan Media Sosial dengan Kualitas Tidur dan Tingkat Stres pada Generasi Z - Iskandar Winata; Nana Rosalina; Supriadi Supriadi (Journal of Medical and Health Science, 2026)
Social media use has become an important part of the daily lives of Generation Z. High intensity of use can have an impact on physical and psychological health, especially related to sleep quality and stress levels. This study aims to analyze the relationship between the intensity of social media use with sleep quality and stress levels in Generation Z. The study used a quantitative approach with a cross-sectional design. The study respondents were Generation Z who actively use social media. Data collection was carried out through a questionnaire that measured the intensity of social media use, sleep quality, and stress levels. The data obtained were then analyzed using correlation analysis to determine the relationship between research variables. The results showed that the intensity of social media use has a significant relationship with sleep quality. Respondents with higher intensity of social media use tend to have lower sleep quality. In addition, the study also found a significant relationship between the intensity of social media use and stress levels. Respondents who use social media more frequently showed higher stress levels compared to respondents who use social media with lower intensity. Other findings showed that poor sleep quality is also related to increased stress levels in respondents. The results of this study indicate that excessive use of social media can impact the sleep health and psychological condition of generation Z. Therefore, managing social media usage time and increasing awareness of digital health are important to support the physical and mental well-being of the younger generation.